(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Key words: RT-PCR, ion imbalance, Binnatoa, transgenic plant D.O.I. 10.3329/ptcb.v19i2.5444 Plant Tissue Cult. & Biotech. 19(2): 257-262, 2009 (December) - Short communication